Pemodelan Pembangkit Listrik Tenaga Angin Untuk Analisis Aliran Daya - Dermanus Niko . (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2017)
Wind farms plant has been developed in many countries especially those having large wind energy potential. If  the  wind  turbine  is  connected /  interconnected grid  power  systems, can  caused  operational problems of the system. Therefore modeling of wind farms to power flow analysis is needed to determine the effect that caused the system. Varied plant located on 5-bus system. then the power system model modified by adding of wind farms on the system, generator used is an induction generator. The method used in this study is Newton-Raphson method and assistance MATLAB program to calculate the power flow in the system Where these calculations are used to determine the effect of wind farms  in the power system. the combining wind farms on one bus in the power system, where the wind turbines have input Pm and output (Pg + jQg), power flow model of the induction generator there are two series impedance, and 1 impedance shunt, so that there exist two internal buses connected to the bus 5. The results obtained in this study is to add wind farms on the system can increase the capacity of power generated on the system.But the impact of this model is the system voltage profile to be ugly,so that the added capacitor bank wind turbine to supply reactive power of induction generator. After the addition of the capacitor bank in wind turbines occurring on the bus voltage is more varied and can improve the voltage profile of the system.   Keywords: Model of wind power in the system, induction generator, Newton-Rapson method